Prevalence and Species Identifications of Camel Ixodid Ticks in Habru District, North Wollo Zone, Northeast Ethiopia - Tsedalu Yirsa; Yidersal Tizazu; Abebe Berihun; Asres Zegeye (Veterinary Medicine and Science)
ABSTRACT Background Ticks are among the most prevalent ectoparasites and carriers of important infectious diseases in animals and people worldwide, particularly in tropical and subtropical regions. Methods A cross‐sectional study from December 2023 to April 2024 sought to determine the incidence and species of camel ixodid ticks in the Habru district. Ticks were categorized into genera and species using morphological identification under a stereomicroscope. Findings A total of 1008 ixodid ticks were collected from 384 randomly selected camels and identified to species level. The overall tick infestation rate was 55.21% in the study camels. Poor body condition and lack of deworming were significantly associated with higher mature tick infestations (p value <0.05). Nevertheless, there were no significant variations in prevalence among animals of different ages (p value >0.05). The most common tick species in this study was Hyalomma dromedarii (28.7%), followed by Amblyomma variegatum (23.02%) and Rhipicephalus pulchelis (21.63%). However, Amblyomma lepidium (4.2%) was the least common tick species. Except for Boophilus decolaratus, all tick species had male‐predominant sex ratios. The maximum tick infection was identified beneath the animals’ tails (30.06%), whereas the lowest infestation was found on the necks (4.46%). Ticks were commonly found across the study area, and animals were afflicted with various ticks. Conclusions Generally, these ticks are well‐known for generating enormous economic losses by transmitting various infectious diseases and disrupting animal health and output. Thus, efficient tick control methods should be adopted in the area.